Whole-genome sequence analysis of Shiga toxin-producing Escherichia coli O157 strains isolated from wild deer and boar in Japan - MORITA, Satoshi; SATO, Shingo; MARUYAMA, Soichi; NAGASAKA, Mariko; MURAKAMI, Kou; INADA, Kazuya; UCHIUMI, Masako; YOKOYAMA, Eiji; ASAKURA, Hiroshi; SUGIYAMA, Hiromu; TAKAI, Shinji; MAEDA, Ken; et al. (Journal of Veterinary Medical Science, 2021)
The prevalence of Shiga toxin-producing Escherichia coli O157 (STEC O157) strains in wild deer and boar in Japan was investigated. STEC O157 strains were isolated from 1.9% (9/474) of the wild deer and 0.7% (3/426) of the wild boar examined. Pulsed-field gel electrophoresis (PFGE) analysis classified the wild deer and boar strains into five and three PFGE patterns, respectively. The PFGE pattern of one wild boar strain was similar to that of a cattle strain that had been isolated from a farm in the same area the wild boar was caught, suggesting that a STEC O157 strain may have been transmitted between wild boar and cattle. Clade analysis indicated that, although most of the strains were classified in clade 12, two strains were classified in clade 7. Whole-genome sequence (WGS) analysis indicated that all the strains carried mdfA, a drug resistance gene for macrolide antibiotics, and also pathogenicity-related genes similar to those in the Sakai strain. In conclusion, our study emphasized the importance of food hygiene in processing meat from Japanese wild animals for human consumption.